Chronic political instability and HIV/AIDS response in Guinea-Bissau - Galjour, Joshua (2021)
BACKGROUND: The Republic of Guinea-Bissau in West Africa has a high HIV/AIDS disease burden and has experienced political instability in the recent past. Our study used qualitative methods to better understand key stakeholders' perceptions of the effects of chronic political instability on the HIV/AIDS response in Guinea-Bissau from 2000 to 2015 and lessons learned for overcoming them. METHODS: Seventeen semi-structured in-depth key informant interviews were conducted in Bissau, Guinea-Bissau in 2018. Interviews were recorded and transcribed verbatim, coded thematically, and analyzed inductively. RESULTS: Four themes emerged: (1) constantly start over; (2) the effects of instability rippling from central level throughout the health pyramid; (3) vulnerable populations becoming more vulnerable; and (4) coping mechanisms. CONCLUSIONS: Stakeholders from government, civil society, and donor organizations have recognized instability's effects as a barrier to mounting an effective local response to HIV/AIDS in Guinea-Bissau. To mitigate the effects of the country's political instability on the health sector, concerted efforts should be made to strengthen the capacities of health officials within the Ministry of Health to shield them from the effects of the country's political instability.